Rethinking markets in modern India : embedded exchange and contested jurisdiction - Gandhi, Ajay, 1976-; Harriss-White, Barbara, 1946-; Haynes, Douglas E.; Schwecke, Sebastian (Cambridge : Cambridge University Press, 2020)
To people operating in India's economy, actually existing markets are remarkably different from how planners and academics conceive them. From the outside, they appear as demarcated arenas of exchange bound by state-imposed rules. As historical and social realities, however, markets are dynamic, adaptative, and ambiguous spaces. This book delves into this intricate context, exploring Indian markets through the competition and collaboration of those who frame and participate in markets. Anchored in vivid case studies - from colonial property and advertising milieus to today's bazaar and criminal economies - this volume underlines the friction and interdependence between commerce, society, and state. Contributors from history, anthropology, political economy, and development studies synthesize existing scholarly approaches, add new perspectives on Indian capitalism's evolution, and reveal the transactional specificities that underlie the real-world functioning of markets.
Markets in modern India : embedded, contested, pliable / Sebastian Schwecke and Ajay Gandhi -- Banking in the bazaar : the Nattukottai Chettiars / David Rudner -- Space in motion : an uneven narrative of urban private property in Bombay / Nikhil Rao -- Magic of business : occult forces in the bazaar economy / Projit Bihari Mukharji -- Vernacular capitalism, advertising, and the bazaar in early twentieth-century western India / Douglas E. Haynes -- The artifice of trust : reputational and procedural registers of trust in north Indian "informal" finance / Sebastian Schwecke -- Mandi acts and market lore : regulatory life in India's agricultural markets / Mekhala Krishnamurthy -- The market and the sovereign : politics, performance, and impasses of cross-LoC trade / Aditi Saraf -- Brandism vs. bazaarism : mediating divinity in Banaras / Andy Rotman -- Black money in India : fighting specters and fostering relations / Ajay Gandhi -- Market making in Punjab lotteries : regulation and mutual dependence / Matthew Hull -- Liquid assets : transactional grammars of alcohol in Jharkhand / Roger Begrich -- Building on sand? Criminal markets and politics in Tamil Nadu / Barbara Harriss-White and J. Jeyaranjan.
Title from publisher's bibliographic system (viewed on 07 Oct 2020).
Keywords: Markets -- India; Bazaars (Markets) -- India; Informal sector (Economics) -- India; India -- Economic conditions